Accounting and indigenous people research for upcoming research agenda - Thahirah, Khadijah Ath; Triyuwono, Iwan; Mulawarman, Aji Dedi; Achsin, M. (Edelweiss Applied Science and Technology, 2025)
This study aims to provide quantitative data on the growth of accounting and indigenous people literature. The analysis focused on the year of publication, country of study, types of methods used, major publishing journal, characteristics of the reviewed articles, keywords and top cited article. The author used bibliometrics and content analysis to explain the evolution and structure of the subject, including co-citation, co-authorship, and bibliographical coupling. The author found that the most relevant country is Australia, the most relevant author is Dean Neu and the most relevant publication is the publication of Accounting, Auditing & Accountability Journal. This study discovered that accounting plays a variety of functions in the marginalization of indigenous peoples. In addition, we offer a number of suggestions for further emancipation-related research that has to be done in order to improve and strengthen the future relationship between accounting and Indigenous people.